New approach to radiation burn treatment by dosimetry-guided surgery combined with autologous mesenchymal stem cell therapy. (September 2007) - Lataillade, JJ; Doucet, C; Bey, E; Carsin, H; Huet, C; Clairand, I; Bottollier-Depois, JF; Chapel, A; Ernou, I; Gourven, M; Boutin, L; Hayden, A; et al.
The therapeutic management of severe radiation burns remains a challenging issue. Conventional surgical treatment (excision and skin autograft or rotation flap) often fails to prevent unpredictable and uncontrolled extension of the radiation necrotic process. We report here an innovative therapeutic strategy applied to the victim of a radiation accident (December 15, 2005) with an iridium gammagraphy radioactive source ( 192 Ir, 3.3 TBq). The approach combined numerical dosimetry-guided surgery with cellular therapy using mesenchymal stem cells. A very severe buttock radiation burn (2000 Gy at the center of the skin surface lesion) of a 27-year-old Chilean victim was widely excised (10 cm in diameter) using a physical and anatomical dose reconstruction in order to better define the limit of the surgical excision in apparently healthy tissues. A secondary extension of the radiation necrosis led to a new excision of fibronecrotic tissues associated with a local cellular therapy using autologous expanded mesenchymal stem cells as a source of trophic factors to promote tissue regeneration. Bone marrow-derived mesenchymal stem cells were expanded according to a clinical-grade technique using closed culture devices and serum-free medium enriched in human platelet lysate. The clinical evolution (radiation pain and healing progression) was favorable and no recurrence of radiation inflammatory waves was observed during the 11 month patient''s follow-up. This novel multidisciplinary therapeutic approach combining physical techniques, surgical procedures and cellular therapy with adult stem cells may be of clinical relevance for improving the medical management of severe localized irradiations. It may open new prospects in the field of radiotherapy complications.